1991
DOI: 10.1097/00003446-199110000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Screening Programs Based on High-Risk Characteristics in Early Identification of Hearing Impairment

Abstract: Prompt identification of educationally significant hearing loss is yet an unattained goal. However, there is some evidence that the ability to identify and diagnose hearing loss at an early age has been significantly improved through the use of carefully designed screening protocols such as birth certificate-based high-risk registries. To evaluate the efficiency of birth certificate-based screening programs, 70 parents and guardians of 6-to 9-yr-old children with significant sensorineural losses were surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 7 publications
(10 reference statements)
5
54
0
2
Order By: Relevance
“…Downs and Sterritt [1964] and Downs and Hemenway [1969] expanded these early nursery-based investigations to evaluate methodology and results of behavioral hearing screening in neonates. Based on behavioral screening of more than 17,000 newborns, Downs and Hemenway reported that 1) their behavioral technique permitted identification of infants with severe-to-profound hearing loss but failed to detect infants with milder forms of hearing impairment, 2) approximately one in 1,000 infants were born deaf, and 3) one-half of the identified infants exhibited risk factors for hearing loss, a finding remarkably similar to later reports [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991].…”
Section: Historical Contextsupporting
confidence: 58%
See 1 more Smart Citation
“…Downs and Sterritt [1964] and Downs and Hemenway [1969] expanded these early nursery-based investigations to evaluate methodology and results of behavioral hearing screening in neonates. Based on behavioral screening of more than 17,000 newborns, Downs and Hemenway reported that 1) their behavioral technique permitted identification of infants with severe-to-profound hearing loss but failed to detect infants with milder forms of hearing impairment, 2) approximately one in 1,000 infants were born deaf, and 3) one-half of the identified infants exhibited risk factors for hearing loss, a finding remarkably similar to later reports [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991].…”
Section: Historical Contextsupporting
confidence: 58%
“…Based on this approach, an infant's hearing is screened only if s/he is identified "atrisk" on the basis of defined criteria such as bacterial meningitis, in utero infection, craniofacial anomaly, or other factors. [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991]. Second, despite wellknown recommendations for screening infants at-risk and decades of advocacy for early identification, the average age of identification for children with hearing loss in the United States stalled at about 12 to 18 months [Stein et al, 1983;Elssman et al, 1987;Stein et al, 1990;Harrison and Roush, 1996].…”
Section: Historical Contextmentioning
confidence: 99%
“…Therefore, screening protocols have focused only on infants at high risks for hearing loss. Since roughly 50% of children with congenital hearing loss do not have an established risk factor, neonates without any risk factors would be lost [9,10]. Ultimately, UNHS is very important and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factor criteria, suggested by the Joint Committee on Infant Hearing (Table 1), are very useful for the recognition and classification of this category of subjects [22]. Regrettably, it has been reported that about 50% of the infantile cases identified with a hearing impairment, do not show none of the JCIH factors [23,24]. Therefore, a hearing screening program based only on the ''babies with JCIH risk factors'' could potentially miss a significant part of the cases presenting hearing impairment.…”
Section: Introductionmentioning
confidence: 99%